The Role of Interactive Methods in Developing Students’ Creative Abilities in Art Education - Muzafarova Sanobar Murodullayevna (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article examines the effectiveness of interactive teaching methods in fostering students’ creative abilities in art education. It highlights the importance of group work, project-based activities, and digital tools in enhancing students’ compositional thinking, aesthetic decision-making, and independent problem-solving skills. The study emphasizes the teacher’s role and the motivational environment in supporting students’ creative potential. Additionally, it analyzes how interactive approaches contribute to the development of both individual and collaborative artistic skills, preparing students for modern professional and academic art contexts.